Evaluating the comparative effects of Listerine zero and Persica mouthwashes on the periodontal conditions of fixed orthodontics patients - Omidsalar, Asal; Emami Meibodi, Shahin; Sayar, Ferena; SheibaniNia, Ahmad (Researcher Bulletin of Medical Sciences, 2023)
Background and Objective: Periodontal problems are very common among patients undergoing fixed orthodontics treatment. Using mouthwashes such as Listerine and Persica is recommended in order to prevent such complications. There have, however, been no information on the comparative effects of Listerine and Persica mouthwashes so far. Thus the comparative study presented here under the title of “Evaluating the comparative effects of Listerine Zero and Persica Mouthwashes on the Periodontal Conditions of fixed orthodontics Patients was conducted at the Department of Dentistry of Azad University of Tehran. Materials and Methods: A blind randomized clinical trial was conducted on 30 patients. All subjects were between 20 and 50 years of age; had been under fixed orthodontic treatment for at least two months; did not have serious systemic health complications; had a minimum of 5 teeth in each quadrant for evaluation. Root planning and scaling were conducted on male and female subjects prior to their entry into the study. The SI, GI, PI, and BOP indices of each subject were then recorded in the base-line stage. The subjects were then divided into two random groups. The first group was treated with Persica (Pursina Co., Iran) and the second group with Listerine Zero (Johnson & Johnson, New Jersey, USA). The two groups were followed up twice after two and four weeks of treatment and their SI, GI, PI, and BOP indices were recorded. Results: The SI, GI, PI, and BOP indices were found to have changed by similar amounts in both groups (P<0.12). The changes in GI, PI, and BOP were, however, statistically significant within each group (P<0.02). The changes in SI index within the Persica group were found to increase only within the first two weeks of treatment (P<0.05). Conclusion: Following the comparative study described above, both mouthwashes appear to positively affect the periodontal condition of fixed orthodontics patients. Both mouthwashes were, however, found to have similar effects.